GLUTAMATE RECEPTORS; FROM BASIC PHARMACOLOGY TO CLINICAL APPLICATIONS: Pharmaceutical Science-Pharmacology - A. ABDEL BAKY, NAYIRA (International Journal of Life Science and Pharma Research, 2022)
The existence of glutamate receptors as important neurotransmitter receptors was not fully accepted until the 1980s. It is now generally agreed that glutamate is the major fast excitatory neurotransmitter in brain, and plays a major role in brain development, affecting neuronal migration, neuronal differentiation, axon genesis, and neuronal survival through its action on the glutamate receptors. There are two classes of glutamate receptors; the ionotropic glutamate receptors (iGluRs), and the metabotropic glutamate receptors (mGluRs). Glutamate receptors are important mediators of a wide range of neuronal functions from primary sensory perception to cognition and also play a role in a number of neurodegenerative diseases. Understanding the role of glutamate in these neurological diseases may highlight treatment potentials of different agonists and antagonists to glutamatergic transmission. In this review, the basic biology of glutamate receptors will be explored. The second part of this article presents a review of the literature for the role of glutamate agonists and antagonists in neurological disease.